The relationship between religiosity and fertility in Developing Countries a comparison of five major religions - Cases, Sheena Kristine M. (Population Institute, College of Social Sciences and Philosophy, University of the Philippines, Diliman, 2019)
Using data on five(5) countries (Thailand, India, Pakistan, Ghana, and Philippines) from Wave 6 (2010-2014) of the World Values Survey, major religions, namely Buddhism, Hinduism, Isla, Protestantism, and Roman Catholicism, were compared. The religion-fertility linkage was explored by comparing six religiosity variables, particularly attendance in a religious service at least once a week, importance put in a religious organization, and praying at least once a day, across major religions. A total justifiability score (TJS) inidcative of conservatism/liberalism, was also computed for each religion by summing up three scores measuring whether respondents consider sex before marriage, abortion, and divorce justifiable. Using Bongaart's Fertility Framework as reference, the relationship of religiosity and the number of children as mediated by the TJS was examined. Count regression (Poison, Negative Binomial, or Zero-inflated count regression) was used to relate religiosity variables and total justifiability scores with fertility indicated by the number of children. Results showed that there is a religion-fertility linkage among Muslims in Pakistan, Hindu in India, and Protestants in Ghana either through one or more religiosity variable or indirectly, the TJS. The total justifiability score significantly predicts the number of children in Muslims in Pakistan and Protestants in Ghana. Using the full model, the religion-fertility link is most apparent for Muslims in Pakistan followed by Hindus in India. Findings can be used to understands how religious practices and beliefs can vary in their effects or lack of effects on fertility measured as the number of children.